Technological development and income inequality: a role of financial marketa - Ichkitidze Yuri; Lushkin Anton; Ungvari Laslo; Akaeva Sadat (SHS Web of Conferences, 2018)
In this paper we study the effects of financial markets on an increase in income inequity. The notion, which is employed as a working hypothesis that the market equilibrium around the fair price and unbiased changes in prices has a neutral effect on inequity while the systematic underreaction accompanied by time trends contributes to its growth, has been considered. In order to check this hypothesis we have studied the long-term cycles in dynamics of the US stock index and income inequity and shown that the stock market growth observed in 1980-2017 is correlated to an increase in income inequity. The presence of causality in this relationship has been found through the evidence of systematic underreaction given by the share prices of fast-growing companies to the information about the diffusion of technological innovations. The research results prove that the free financial markets with technological development in progress contribute to instability, as they while enhancing income inequality increase the unemployment growth risks and require additional efforts from the state to redistribute income.